Legacy of Nehru - Singh,K.Natwar (ed.) (New Delhi, 2006)
How a variety of notable and thoughtful people in many countries viewed the achievements of one of the world`s greatest men and grieved at his loss, forms the substance of this book.
Keywords: "Nehru, Jawaher Lal"